Lysyl oxidase interactions with transforming growth factor‐β during angiogenesis are mediated by endothelin 1. Issue 9 (9th August 2021) - Grunwald, Hagar; Hunker, Kristina L.; Birt, Isabelle; Aviram, Rohtem; Zaffryar‐Eilot, Shelly; Ganesh, Santhi K.; Hasson, Peleg
Abstract: Crosstalk between multiple components underlies the formation of mature vessels. Although the players involved in angiogenesis have been identified, mechanisms underlying the crosstalk between them are still unclear. Using the ex vivo aortic ring assay, we set out to dissect the interactions between two key angiogenic signaling pathways, vascular endothelial growth factor (VEGF) and transforming growth factor β (TGFβ), with members of the lysyl oxidase (LOX) family of matrix modifying enzymes. We find an interplay between VEGF, TGFβ, and the LOXs is essential for the formation of mature vascular smooth muscle cells (vSMC)‐coated vessels. RNA sequencing analysis further identified an interaction with the endothelin‐1 pathway. Our work implicates endothelin‐1 downstream of TGFβ in vascular maturation and demonstrate the complexity of processes involved in generating vSMC‐coated vessels.